BUDAYA MELUKADE SEBAGAI CARA PASTORAL KONSELING MENJADI CIRI MODERASI BERAGAMA ORANG NUSA UTARA - Yohan Brek; Brayen Vicard Bulamei (Institut Agama Kristen Negeri Manado, 2023)
This research aims to find, analyze and elaborate the ideal idea of melukade culture which is used as a method of pastoral counseling and then becomes a characteristic of the religious moderation of the people of North Nusa. Researchers used descriptive qualitative research methods in carrying out analytical work. From the results of scientific work, the ideal idea was found which resulted in the perception, impact and implementation of melukade culture as a way of pastoral counseling to characterize the religious moderation of the people of North Nusa.